The GPR139 agonist TAK-041 produces time-dependent alterations to cerebral blood flow and reward system function in patients with schizophrenia: a randomised placebo-controlled trial - Peter C. T. Hawkins; Adam J. Schwarz; James M. Stone; Fiona Pepper; James Gilleen; Sam Gijsen; Ndabezinhle Mazibuko; Dimitrios Arkilo; Wei Yin; Jingtao Wu; Polyna Khudyakov; Rhett Behrje; et al. (Psychopharmacology, 2026)
The negative and cognitive symptoms of schizophrenia are predictive of quality of life and functional recovery, but there are no approved drug options that target these symptoms directly. TAK-041 (also known as NBI-1065846) is a selective and potent small-molecule agonist of GPR139, an orphan G-protein-coupled receptor, which has been shown to reverse deficits related to negative and cognitive symptoms in animal models. In this proof-of-activity study to evaluate the effects of TAK-041 on motivational anhedonia, 23 adults with schizophrenia experiencing moderate to severe negative symptoms were administered a single 40 mg or 160 mg dose of TAK-041 in a randomised, double-blind, placebo-controlled, two-period crossover design. Functional magnetic resonance imaging (fMRI) assessment of reward function (monetary incentive delay [MID] task) and cerebral blood flow (CBF), as well as cognitive assessment with the Brief Assessment of Cognition in Schizophrenia (BACS) tool, were performed 3 h post dose and after 14 days. There was no significant effect of TAK-041 compared with placebo on BACS score at either timepoint. There was also no significant effect of TAK-041 on MID fMRI at day 1; however, at day 14, TAK-041 produced an increase in reward anticipatory activity in the ventral striatum compared with placebo. There was a significant decrease in CBF throughout the brain at day 1 that then reversed, resulting in a relative increase at day 14, compared with placebo. At day 14 there was a significant interaction between drug and CBF on reward anticipatory BOLD, indicating that drug-related changes to CBF may partially contribute to the observed BOLD effects (although the main effect of drug on the BOLD signal remained significant after including CBF as a covariate in the model). These data indicate that TAK-041 produces detectable changes in both CBF and reward task related fMRI signal in brain regions linked with symptoms and treatment response in schizophrenia. IND Number: 130074| EudraCT Number: 2017-001084-20| Clincaltrails.gov registry: NCT03319953.